1981
DOI: 10.1128/aac.19.2.226
|View full text |Cite
|
Sign up to set email alerts
|

Comparative toxicity of amantadine hydrochloride and rimantadine hydrochloride in healthy adults

Abstract: The relative toxicities of amantadine and rimantadine were compared in a double-blind, placebo-controlled study involving healthy adults. In separate studies, drugs were administered at a dosage of 200 mg/day (52 volunteers) or 300 mg/day (196 volunteers) Clinical trials have documented that amantadine hydrochloride (7,11,14,17,18,22 483, 1978) and rimantadine hydrochloride (6,11,26,33) are effective prophylactic and therapeutic drugs in influenza A virus infections. Several in vitro (10, 31) and animal (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
61
0

Year Published

1983
1983
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(62 citation statements)
references
References 31 publications
1
61
0
Order By: Relevance
“…Van Voris and co-workers (16) found that 33% of amantadine recipients experienced minor central nervous system side effects by day 5 of therapy, but less than 5% failed to take all medications. Hayden et al (9) concluded that 200 mg of amantadine daily was very well tolerated by healthy volunteers over a short treatment period, although 300 mg daily lead to unacceptable side effects. Bryson et al (2) also described central nervous system side effects in 33% of a large group of college students treated with 200 mg of amantadine daily for 4 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Van Voris and co-workers (16) found that 33% of amantadine recipients experienced minor central nervous system side effects by day 5 of therapy, but less than 5% failed to take all medications. Hayden et al (9) concluded that 200 mg of amantadine daily was very well tolerated by healthy volunteers over a short treatment period, although 300 mg daily lead to unacceptable side effects. Bryson et al (2) also described central nervous system side effects in 33% of a large group of college students treated with 200 mg of amantadine daily for 4 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Until recently, the adjuncts to vaccination were limited to the use of the M2 inhibitors amantadine or rimantadine. However, their use has not gained wide acceptance due in part to their ine¡ectiveness against in£uenza B, the rapid emergence of drug-resistant variants Hayden et al 1989;Hayden 1994) and their poor adverse event pro¢le (Hayden et al 1981(Hayden et al , 1983. Furthermore, the e¡ectiveness of amantadine or rimantadine in severe in£uenza or in patients at high risk of developing in£uenza-related complications is uncertain.…”
Section: Introductionmentioning
confidence: 99%
“…Several adamantane derivatives are currently used as e cient therapies against in uenza [3][4][5], herpes simplex [6] and HIV [7][8][9] viruses. In addition, numerous adamantane derivatives were reported to exhibit marked anticancer [10,11], antibacterial [12][13][14][15] and antifungal [16] activities.…”
Section: Discussionmentioning
confidence: 99%